ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN PT. CHAMP RESTO INDONESIA TBK PERIODE 2022-2024 - Ria Febrianti; Achmad Wicaksono (Universitas Logistik dan Bisnis Internasional, 2026)
This study aims to analyze the financial performance of PT Champ Resto Indonesia Tbk through financial ratio analysis. Adopting a descriptive quantitative methodology, the study examines secondary data derived from the entity’s annual reports between 2022 until 2024, sourced from the official website of the Indonesia Stock Exchange (IDX). The analysis applies liquidity, solvency, activity, and profitability ratios to assess the company’s financial condition and performance. The results indicate that the company’s liquidity ratios are below the ideal standard, reflecting limited ability to meet short-term obligations. From a solvency perspective, the company’s capital structure is largely dominated by debt, resulting in higher leverage and increased financial risk. Activity ratios reveal that asset utilization in generating sales has not been optimal, while profitability ratios show a declining trend, indicating a weakening ability to generate profits despite an increase in revenue. Based on these findings, it can be concluded that the financial performance of PT Champ Resto Indonesia Tbk during the research period experienced financial pressure, highlighting the need for evaluation and improvement in financial management. Financial ratio analysis is proven to be effective in providing an overview of the company’s financial condition and performance and can serve as a basis for managerial decision making.